Methods for wine fraud detection - Kuzinska, Vladyslava; Ishchenko, Vera (My University, 2023)
According to the Decernis Food Fraud Database, wine is among the top three most adulterated beverages. Because of its high prices, it is a prime target for adulteration, which can occur at any stage of its production or sale. The addition of cheap ingredients, dilution with water, adulteration and mislabeling are the most common types of wine fraud. Finding an accurate way to detect counterfeiting of this product can sometimes be difficult, time-consuming and expensive. Today, there are numerous analytical methods for wine identification that involve the use of specific marker compounds, stable isotope ratio measurements, and/or chromatography. They make it possible to identify the geographical origin, variety and method of production of this product. This study characterizes these methods of detecting wine adulteration.

Згідно з базою даних Decernis Food Fraud Database, вино входить до трійки найбільш фальсифікованих напоїв. Через високі ціни воно є основною мішенню для фальсифікації, яка може статися на будь-якому етапі його виробництва чи продажі Додавання дешевих інгредієнтів, розведення водою, підробка та неправильне маркування є найпоширенішими видами шахрайства вина. Пошук точного способу виявлення фальсифікації цього продукту іноді може бути складним, тривалим і дорогим. Сьогодні є численні аналітичні методи для ідентифікації вина, які передбачають використання специфічних маркерних сполук, вимірювання співвідношення стабільних ізотопів та/або хроматографію. Вони дозволяють виявити географічне походження, сорт і спосіб виробництва цього продукту. В даному дослідженні схарактеризовані ці методи виявлення фальсифікації вина.
Keywords: кафедра харчової хімії; chromatographic analysis; хроматографічний аналіз; фальсифікація вина; wine adulteration